Improving Pediatric Extracorporeal Cardiopulmonary Resuscitation Means Delivering Best Care and Measuring Impact Beyond Survival - Barbaro R.P. (Lippincott Williams and Wilkins, 2019)
10.1097/CCM.0000000000003673